Development of a Bioelectrochemical System as a Tool to Enrich H2-Producing Syntrophic Bacteria - Guzman, Juan J. L.; Sousa, Diana Z.; Angenent, Largus T. (Frontiers in Microbiology, 2019)
Syntrophic microbial partnerships are found in many environments and play critical roles in wastewater treatment, global nutrient cycles, and gut systems. An important type of syntrophy for the anaerobic conversion of carboxylic acids is H2 syntrophy. In this type of microbial partnership, dissolved H2 is produced by a bacterium and rapidly consumed by an archeon (methanogen), resulting in methane gas. This is referred to as interspecies H2 transfer, and some conversions rely on this mechanism to become thermodynamically feasible. For this reason, syntrophic partners are often not possible to separate in the lab, which hampers the full understanding of their physiology. Bioelectrochemical systems (BESs) may show promise to ultimately separate and study the behavior of the syntrophic bacterium by employing an abiotic H2 oxidation reaction at the anode, actively removing dissolved H2. Here, we performed a proof-of-concept study to ascertain whether an H2-removing anode can: 1) provide a growth advantage for the syntrophic bacterium; and 2) compete with the methanogenic partner. A mathematical model was developed to design a BES to perform competition experiments. Indeed, the operated BES demonstrated the ability to provide a growth advantage to the syntrophic bacterium Syntrophus aciditrophicus compared to its methanogenic partner Methanospirillum hungatei when grown in co-culture. Further, the BES provided the never-before isolated Syntrophomonas zehnderi with a growth advantage compared to Methanobacterium formicicum. Our results demonstrate a potential to use this BES to enrich H2-sensitive syntrophic bacteria, and gives prospects for the development of an effective method for the separation of obligate syntrophs.